Correlation between brain natriuretic peptide levels and the prognosis of patients with left ventricular diastolic dysfunction - GONG, HUI (Exp Ther Med, 2016)
The present study aimed to investigate the association between brain natriuretic peptide (BNP) levels and the prognosis of patients with left ventricular (LV) diastolic dysfunction. A total of 708 inpatients with cardiovascular disease (mean age, 66 years; 395 males and 313 females) were grouped according to initial BNP and were followed-up for 20–51 months (average, 30.86 months) until endpoint events occurred. Endpoints were defined as mortality or readmission due to cardiovascular disease, or mortality due to any other reason. A total of 67 and 77 events were reported in the BNP ≤80 pg/ml and BNP >80 pg/ml groups, respectively. The occurrence rate of the endpoint was significantly higher in the BNP >80 pg/ml group, as compared with the BNP ≤80 pg/ml group (26.28 vs. 16.14%; relative risk=1.63). Furthermore, the durations of patient survival were significantly shorter in the BNP >80 pg/ml group, as compared with the BNP ≤80 pg/ml group (P=0.0006), and patient survival decreased as BNP levels rose (P=0.0074). Among the 708 patients, 677 underwent echocardiographic detection at the same time. No significant correlation was detected between BNP levels and survival time in 178 patients with normal LV diastolic function [mitral Doppler flow, early diastolic (E)/late diastolic (A)>1] (P=0.2165); whereas a negative correlation was determined in 499 patients with LVD dysfunction (E/A≤1) (Spearman's rho=−0.0899; P=0.0447). The prognoses of patients with elevated BNP levels were correspondingly worse in the present study and these correlations were demonstrated to be significant in patients with LV diastolic dysfunction. Therefore, BNP levels may be used to predict the prognosis of patients with cardiovascular disease.